LIQUID HOLDUP MANAGEMENT BY PREDICTING STEADY STATE TURNDOWN RATE IN WET GAS PIPELINE NETWORK - kartika fajarwati hartono; Muhammad Taufiq Fatthadin; Reno Pratiwi (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2016)
Now days, one of the greatest challenges in gas development is transport the fluid especially multiphase fluid to long distances and multiphase pipeline to sell point. Yet, a challenge to transport multiphase fluid is how to operate the systemsin operating a long distance, large diameter, and multiphase pipeline.The operating system include how to manage high liquid holdup, mainly built during low production rate (turn down rate) periods especially during transient operations such as restart and ramp-up, so that liquid surge arriving onshore will not exceed the liquid handling capacity of the slug catcher. The objective of this research is to predict liquid trapped in pipeline network by analysis turn down rate in order to determine minimal gas production rate for stable operation. This research was carried out by two steps: Simulation Approach and Optimization Techniques. Simulation approach include define fluid composition and built pipeline network configuration while optimization technique include conduct scenario for turn down rate. The fluid composition from wellhead to manifold is wet gas. First scenario and Second scenario of turndown rate yield minimum gas rate for stable operation. The pipeline has to be operated above 600 MMSCFD from peak gas production rate is 1200 MMSCFD (A-Manifold Mainline) and 60 MMSCFD from peak gas production rate is 150 MMSCFD for D-Manifold Mainline.